Glottochronological Classification of Oromo Dialects - Blažek, Václav (Lingua Posnaniensis, 2011)
The purpose of the present article is the classification of the Oromo dialect continuum. Firstly, the previous attempts are discussed. As a method the so-called ‘recalibrated glottochronology’ developed by Sergei Starostin was applied. The results confirm the mutual relation of the ‘mainstream’ dialects, Maca, Qottu and Borana. In the case of more peripheral dialects the differences are bigger in comparison with the ‘impressionistic’ model sketched in Ethnologue16 (Bender compared only those three dialects). The reason probably consists in the chosen method: although it is not explicitly said in Ethnologue16, the classification used combines the qualitative and geographical approaches, contrary to the present model based on strictly quantitative principles.